Role of Rigid Medical Thoracoscopy in Diagnosing Exudative Pleural Effusions with Low Adenosine Deaminase (Academia Journal of Medicine, 2021)
Background: Medical thoracoscopy (MT) performed in the evaluation of undiagnosed exudative pleural effusion (EPE) has a high diagnostic yield. In this study, we describe our experience of rigid MT in the evaluation of undiagnosed exudative pleural effusions (EPE) with low adenosine deaminase (ADA). Subjects and Methods:This is a retrospective analysis of RT pleural biopsies performed between July 2012 and June 2015 for diagnosing EPE. These patients had at least two pleural fluid samples negative for malignant cytology and ADA less than 65 IU/L. Here we report the yield and complications of pleural biopsies with RT. Results: Our yield of thoracoscopic pleural biopsies was 81% with malignancy as the commonest diagnosis in 46% patients. Malignant pleural effusion was caused commonly by adenocarcinoma (67%) followed by squamous cell carcinoma (17%), small cell lung cancer (8%) and lymphoma (8%). There was no case of mesothelioma. Biopsy revealed tuberculosis in 31%, vasculitis in 4%, nonspecific pleuritis (NSP) in 11% and normal pleural tissue in 8% subjects. The presence of nodules on CT scan and those on MT had no significant correlation (P > 0.1). ADA did not significantly differ between various biopsy confirmed diagnostic groups (P > 0.2). Minor complications that settled with conservative management developed in 3 patients (11.5%) and were significantly related to comorbidities (p < 0.05) but not to the biopsy result (P = 0.894). Conclusion: Since majority of the EPE turn out to be either malignancy of tuberculosis, a rigid MT evaluation should be considered in all such patients if the facility is available at the center. Rigid MT has high diagnostic yield and acceptable safety.
Keywords: Rigid thoracoscopy; medical thoracoscopy; pleuroscopy; pleural effusion; ADA; tuberculosis; lung malignancy